SCLEROCHRONOLOGICAL RECORDS OF ARCTICA ISLANDICA FROM THE INNER GERMAN BIGHT - Epple V.M.; Brey T.; Witbaard R.; Kuhnert H.; Patzold Ju. (My University, 2006)
Sclerochronological records of interannual shell growth variability were established for eight modern shells (26 to 163 years of age) of the bivalve Arctica islandica, which were sampled at one site in the inner German Bight. The records indicate generally low synchrony between individuals. Spectral analysis of the whole 163-yr masterchronology indicated a cyclic pattern with a period of 5 and 7 years. The masterchronology correlated poorly to time series of environmental parameters over the last 90 years. High environmental variability in time and space of the dynamic and complex German Bight hydrographic system results in an extraordinarily high ‘noise’ level in the shell growth pattern of Arctica islandica.
Keywords: ARCTICA ISLANDICA; GERMAN BIGHT; SCLEROCHRONOLOGY; TIME SERIES; ENVIRONMENTAL VARIABILITY; SPECTRAL ANALYSIS; MASTER-CHRONOLOGY